Implementation Strategies for the Indonesian 3S Nursing Framework (SDKI, SIKI, and SLKI) in Clinical Practice: A Scoping Review - Wisuda, Aris Citra; Suraya, Citra; Oxyandi, Miming (International Journal Scientific and Professional, 2025)
The Indonesian 3S Nursing Framework—comprising the Nursing Diagnosis (SDKI), Nursing Interventions (SIKI), and Nursing Outcomes (SLKI)—was developed to standardize nursing care and enhance patient safety. Despite its formal adoption, implementation across Indonesian clinical settings remains inconsistent. This scoping review aims to identify and map strategies for implementing the 3S Framework in clinical nursing practice. Following PRISMA-ScR guidelines, a systematic search was conducted across Garuda, CINAHL, ScienceDirect, and Google Scholar for articles published between 2020 to 2025. From 1,356 articles, 12 met the inclusion criteria. Seven key strategies were identified: structured training programs, case study discussions, mentoring, use of standardized instruments, observational learning, innovative methods (e.g., simulation, role-play), and institutional support through policy and system integration. These approaches improved nurses' knowledge, skills, documentation accuracy, and patient safety. Challenges included institutional variability, limited monitoring, and unfamiliarity with the 3S components. Comprehensive strategies integrating education, mentorship, innovation, and institutional support are essential for effective implementation. Future efforts should focus on developing national guidelines, evaluation tools, and sustainable training models to support widespread adoption.